Screening for Pectin and making of jam from potential parts of honeydew fruit - Yusof, Nurlina; Jamal, Parveen; Jaswir, Irwandi (2012)
Pectin is a polymer which contains at least 65% of galacturonic acid. It can be found only in plants and function as the gelling agent. Although research on pectin is common, but no report is there for the extraction of pectin from the honeydew. Honeydew melon (Cucumis Melo I.) is a seasonal fruit, which has unique and sweet taste and originated from France. This research sought to screen pectin content from different parts of honeydew. Three parts of honeydew, which comprises of the outer skin, inner skin and fruit pulp were used in this research. 200 g of Honeydew, 214 ml of water and 7 ml of lemon juice were employed during the process and 95% alcohol was used for precipitation activity. From this study, inner skin of honeydew was found to possess a higher amount of pectin. Different parts of honeydew fruits were later used in jam making. Four different types of honeydew jams were prepared; two jams from the inner skin (with and without added pectin) and the other two jams from the fruit pulp (with and without added pectin). Out of the 20 respondents participated in sensory evaluation, 78% reckoned that jam from the inner skin (the part that is usually considered as waste) without the added pectin is favourable to jam making.